1991
DOI: 10.1073/pnas.88.21.9813
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation kinetics of the transduction cascade of vision.

Abstract: The response of the retinal rod ceil to a dim flash lasts less than a second. This phototransduction is mediated by a guanine nucleotide-binding (G) protein cascade in which rhodopsin is the receptor, transducin is the G-protein, and the cGMP-specific phosphodiesterase (PDE) is the effector. Photoexcited rhodopsin activates transducin which in turn activates PDE. For this underlying biochemistry to be kinetically compatible with the photoresponse, both transducin and PDE must be deactivated in subsecond times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…This is reached after a (3). As for k+, it is indeed much larger than kR and is comparable with some theoretical values reported elsewhere (28,29).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This is reached after a (3). As for k+, it is indeed much larger than kR and is comparable with some theoretical values reported elsewhere (28,29).…”
Section: Resultssupporting
confidence: 74%
“…As for the difference between k+ and kR, it is huge since kR cannot be much more than a few s-1. Rokpt, for t < [3] This confirms that the rising slope is directly proportional to the illumination level R(, the proportionality constant being kp, the rate constant for the production of PDE*. Moreover, this rising phase is independent of kR, i.e.…”
Section: Resultssupporting
confidence: 63%
“…From studies on Gk activation of the cardiac K + currents (lktm)) [30] it has been observed that the k,~,, determined from the rate of decay oflk(M) is over 100 min -~, whereas this value is about 2 rain -I in purified preparations of Gi or Go [14,31]. A similar mechanism, where the effector (phosphodiesterase) accelerates the normally slow rate of GTP hydrolysis by a heterotrimeri¢ G-protein (transducin) has recently been proposed [32,33]. In addition, there exists a family of GAPs which stimulate the very slow endogenous GTP hydrolysis by small Q.proteins, including p21 "~ (reviewed in [14]), and may also act as effectors for this G-protein [34].…”
Section: Discussionmentioning
confidence: 99%
“…Purified G␣ subunits display a measurable intrinsic rate of GTP hydrolysis, but the turnover number in vitro cannot account, in some systems, for the rate at which signaling is terminated in vivo (16,17). Other regulatory processes (such as those mediated by arrestin or phosducin) could be rate-limiting.…”
Section: The Cycle Of G Protein Activation and Inactivationmentioning
confidence: 99%